Guidelines on suicide amongst anaesthetists 2019. (14th November 2019) - Shinde, S.; Yentis, S. M.; Asanati, K.; Coetzee, R. H.; Cole‐King, A.; Gerada, C.; Harding, K.; Hawton, K.; Hennessy, A.; Keats, P.; Kumar, N.; McGlennan, A.; et al.
Summary: Anaesthetists are thought to be at increased risk of suicide amongst the medical profession. The aims of the following guidelines are: increase awareness of suicide and associated vulnerabilities, risk factors and precipitants; to emphasise safe ways to respond to individuals in distress, both for them and for colleagues working alongside them; and to support individuals, departments and organisations in coping with a suicide.